Pelatihan Pemanfaatan Aplikasi Canva untuk Pembelajaran Interaktif di Bimbingan Belajar Anak Hebat Cabang Cibarusah - Ermanto, Ermanto; Fatchan, Muhamad; Aprila Hardi, Resty; Suryadi (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
The "Utilization of the Canva Application for Interactive Learning" training was held at the Cibarusah Branch of the Great Children's Tutoring Center (Bimbingan Belajar Anak Hebat) as an effort to improve educators' competency in utilizing digital technology to support the learning process. This activity was motivated by the need for teachers and tutors to provide learning media that are more engaging, interactive, and easy for students to understand. The training method was a workshop approach, combining theory and hands-on practice using the Canva application. Participants were guided in creating various interactive media, such as presentations, infographics, visual materials, and evaluation content tailored to children's learning needs. The training results demonstrated improved skills in designing creative learning media and increased motivation to integrate technology into teaching and learning activities. This training is expected to make the learning process at the Cibarusah Branch of the Great Children's Tutoring Center more effective, enjoyable, and able to encourage active student participation. Keywords: Canva, Interactive Learning, Digital Media, Tutoring, Teacher Training.